An Integrative Approach to Treat Parkinson's Disease: Ukgansan Complements L-Dopa by Ameliorating Dopaminergic Neuronal Damage and L-Dopa-Induced Dyskinesia in Mice - Huh, Eugene; Choi, Jin Gyu; Sim, Yeomoon; Oh, Myung Sook (Frontiers in Aging Neuroscience, 2019)
Parkinson’s disease (PD) is accompanied by motor impairments due to the loss of dopaminergic neurons in the nigrostriatal pathway. Levodopa (L-dopa) has been the gold standard therapy for PD since the 1960s; however, its neurotoxic features accelerate PD progression through auto-oxidation or the induction of dyskinetic movements. Ukgansan (UGS) is a well-known prescription for treating PD in traditional medicines of East Asia, and its anti-PD function has been experimentally evaluated. The present study investigated whether UGS attenuates (1) motor dysfunction and dopaminergic neuronal damage when co-treated with L-dopa and (2) L-dopa-induced dyskinesia (LID) in 6-hydroxydopamine (6-OHDA)-induced PD mice. Although L-dopa was found to reduce motor dysfunctions, it failed to decrease the dopaminergic neuronal damage and increased the expression of dopamine receptor 1 (D1R) and 2 (D2R) in the 6-OHDA-injected mouse striatum. Co-treatment with UGS resulted in normal striatal histology and ameliorated motor impairments. In addition, UGS suppressed the dyskinesia induced by chronic L-dopa treatment while restoring the dopaminergic neurons in the striatum. For the underlying mechanism, UGS reduced the overexpression of D1R-related signaling proteins, such as phosphorylated extracellular signal-regulated kinase, ∆FosB, and c-fos in the striatum. Overall, the results suggest that the effect of UGS could be complementary to L-dopa by ameliorating motor dysfunction, restoring the dopaminergic neurons, and suppressing the dyskinetic movements in PD.